Spatial relevance for the development of desert cities in Anbar province: (Al-Waleed District as a pattern) - Al-Kubeisy, Amjad Raheem M. (Al-Adab Journal, 2019)
Regions differ and vary widely according the nature of environment and topography and the pattern of social and economic relations including desert regions which are characterized by special environmental characteristics besides its distinctive pattern of social relations. the pattern of desert regions which have hot and dry climate 70% from the total land of Iraq. Those regions, thus, suffer from the lack of adopting the pattern of regional planning and, also, the squander of the economic resources and the decadence of the social states. The economic development of any country depends on the extent of planning of investing and maintaining the natural resources to be employed in serving the environment and achieving the persistent and balanced development. In order to raise the population and environmental states of the desert regions, it is supposed to adopt special planning programs within the comprehensive and developmental planning programs of countries by not leaving any deserted areas like the weakness areas in order to ensure the natural extension of constructional development in the future. It is developed through the its available natural resources to consolidate the national economy by establishing human settlements which contribute to achieve settlement and avoid spatial isolation.